The effect of uterine and spiral artery Doppler velocimetry in predicting miscarriage in threatened miscarriage patients - Tanrıdan Okçu, Nefise; Gürbüz, Tuğba (Journal of Surgery and Medicine, 2021)
Background/Aim: Doppler sonography was used to investigate the effect of abnormal placentation on early and late pregnancy complications with conflicting results on changes in uterine blood flow and spiral arteries in early pregnancy. This study aimed to compare the uterine and spiral artery Doppler findings between healthy pregnant women and patients with threatened miscarriage. Methods: In this prospective case-control study, the uterine and spiral artery Doppler findings of 60 patients with threatened miscarriage between 12-20 weeks of gestation were compared with those of 60 healthy pregnant women at similar gestational weeks. Resistance index, spiral artery pulsatility index, systolic/diastolic ratio, and uterine artery Doppler values were evaluated. Results: The patients in the threatened miscarriage group had a higher mean age than those in the control group (P<0.001). No significant difference was found between the groups in terms of uterine artery and spiral artery resistance index, systolic/diastolic ratio, and pulsatility index values (P>0.05 for each). Conclusions: Our results showed that there was no significant difference between the indexes of spiral and uterine artery in Doppler ultrasonography. Further studies are needed to evaluate uterine vascular bed alterations to predict the threatened miscarriage prognosis in the first trimester.